In their own words: a qualitative study of factors promoting resilience and recovery among postpartum women with opioid use disorders - Daisy J. Goodman; Elizabeth C. Saunders; Kristina B. Wolff (BMC, 2020)
Abstract Background Opioid use disorder (OUD) is associated with substantial morbidity and mortality for women, especially during the perinatal period. Opioid overdose has become a significant cause of maternal death in the United States, with rates highest in the immediate postpartum year. While pregnancy is a time of high motivation for healthcare engagement, unique challenges exist for pregnant women with OUD seeking both substance use treatment and maternity care, including managing change after birth. How women successfully navigate these barriers, engage in treatment, and abstain from substance use during pregnancy and postpartum is poorly understood. The aim of this study is to explore the experiences of postpartum women with OUD who successfully engaged in both substance use treatment and maternity care during pregnancy, to understand factors contributing to their ability to access care and social support. Methods We conducted semi-structured, in-depth interviews with postpartum women in sustained recovery (n = 10) engaged in a substance use treatment program in northern New England. Interviews were analyzed using grounded theory methodology. Results Despite multiple barriers, women identified pregnancy as a change point from which they were able to develop self-efficacy and exercise agency in seeking care. A shift in internal motivation enabled women to disclose need for OUD treatment to maternity care providers, a profoundly significant moment. Concurrently, women developed a new capacity for self-care, demonstrated through managing relationships with providers and family members, and overcoming logistical challenges which had previously seemed overwhelming. This transformation was also expressed in making decisions based on pregnancy risk, engaging with and caring for others, and providing peer support. Women developed resilience through the interaction of inner motivation and their ability to positively utilize or transform external factors. Conclusions Complex interactions occurred between individual-level changes in treatment motivation due to pregnancy, emerging self-efficacy in accessing resources, and engagement with clinicians and peers. This transformative process was identified by women as a key factor in entering recovery during pregnancy and sustaining it postpartum. Clinicians and policymakers should target the provision of services which promote resilience in pregnant women with OUD.